Implementation of Langsa City Qanun No. 1 of 2015 Concerning Smoke-Free Areas Reviewed from Constitutional Law (Case Study of Langsa City Health Center) - Tasya Mirza (Tunas Institute, 2024)
There is a gap between practice and theory where people still smoke in the health center area which is one of the health facilities in the smoke-free area in accordance with Qanun No. 1 of 2015. The purpose of this study is to see (1) How is the implementation of Qanun Langsa City No. 1 of 2015 concerning the Smoke-Free Area in the Langsa City Health Center. (2) How is the implementation of Qanun Langsa City No. 1 of 2015 concerning the Smoke-Free Area in the Langsa City Health Center Reviewed from Constitutional Law. This study uses qualitative research with data collection methods through observation, interviews, and documentation. The results of the study indicate that (1) The implementation of the Smoke-Free Area Policy in the Langsa City Health Center has been running quite well but not yet optimal even though things such as socialization and installation of stickers and banners have been carried out properly in an effort to organize the Smoke-Free Area, but there have been no strict sanctions given to violators, so that the Smoking Area policy has not been fully implemented properly. (2) If viewed in terms of fiqh siyasah, the implementation of the No-Smoking Area Policy at the Langsa City Community Health Center is in accordance with the concept of fiqh siyasah which aims for the benefit of the people, but the implementation and supervision process has not yet gone completely well.